KUALITAS PELAYANAN PUBLIK PADA MOBIL UNIT PELAYANAN SIM KELILING DI KOTA PEKANBARU - Maria Yulita; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
New public service (NPS) ia a consept of democratic public service, fair equality, not discriminatory, honest and accountable, by quaranteeing community rights and fulfilling their responsibities to the community by pririotizing the unterest of the community. One of the services that should use the NPS concept is a service unit cars of driver licence. that is a special vehicles that has assign to driver licence extenntion service by visiting the location of public area with a customized service scehedule at public consideration. The goal of this research is exploring the quality of public service on service unit cars of driver licence in Pekanbaru city. The concept theory used in this study was the theory dimentions of public servicequality by Tjiptono, in terms of timeliness of service, accuracy of service, countesy and friendliness, ease of service, confort in obtaining service and supporting atributes. This researhc was a qualitative descriptive, method with purposive sampling techniques with observation, interview, library study, and dokumentation as the techniques of collecting data. This research showed that quality of public service on services on service unitc cars of driver licence in Pekanbaru city has been running but it is still not optimal and the there needs to add officers on duty around the cars of driver and complete supporting facilities and infrastructure so that services can go up again so that people who make driver licence extensions on cars of driver feel satisfied with the services provided. Keywords: Quality of Service, Public Service, Service Cars Of Driver Licence